Energy-efficient technologies and their application in the budgetary sphere. (Journal of Economic Research & Business Administration, 2016)
The problems of energy saving and energy efficiency are among the top priorities of public policy in Kazakhstan. The rising cost of energy makes energy efficiency investments more attractive. However, Kazakhstan remains one of the most energy-intensive economies in the world. The organizations of the budgetary sphere consume about 5% of the electric power developed in the country and about 15% of thermal energy, also by expert estimates consumption of primary energy resources makes to 5% of the general consumption of the country. Thus, the budgetary sphere is not the large consumer of energy carriers. However, the social importance of the budgetary sphere and its insufficient financing sharply puts a problem of rational consumption of energy carriers, their account and economy. Main objective of energy saving is realization of strategy of complex effective use of energy resources at sustained economic growth both steady improvement of quality of life and preservation of healthy environment. And today the special part is assigned to questions energy saving promotion as knowledge, the high culture of energy saving of people determines the level of efficiency of use of energy resources in the majority. Energy saving becomes a synonym of a sustainable development since positively influences and an ecological situation – due to decrease in need for new capacities and use of new technologies. Losses of energy in the cities and the industry are idle capital, the main source of decrease in expenses today. In this regard in the present to article energy efficiency problems reveal, acts are analysed, complex measures for improvement of energy efficiency in the budgetary orgnanization are formulated. Also in work are considered experiment of foreign countries on studying and use in practice of the principles and methods of energy saving, recommendations about development power effective technologies are made.
Keywords: energy efficiency; budget organizations; energy resources; modernization; reduction of energy losses; energy audit.